Impact assessment of unified agricultural extension system on agroforestry development in Oyo State, Nigeria (2000)
The study assessed the impact of the unified agricultural extension system (UAES) on the adoption of agroforestry (AF) technologies in Oyo state, Nigeria. Modified stratified multistage random sampling technique was used, employing two sets of open-ended and structured questionnaires as the study tool. Study populations were the farmers and extension agents (EAs) under Oyo State Agricultural Development program (OYSADEP). One Hundred and Twenty-Five (125) and Ninety (90) questionnaires respectively were administered on the Farmers and Extension Agents, randomly selected from thirty (30) percent of the total number of cells in each block under OYSADEP's administrative zones Descriptive and chi-square statistics were used to analyse the data generated. The analyses revealed that seventy (70) percent of the extension personnel interviewed who had spent between five and ten years in service knew little or nothing about agroforestry. Also, less than half of the respondents (47.8%) were introduced to farm forestry by OYSADEP extension agents Apart from this, more than ninety-six percent of the farmers were found to be male, with most of them (71.5%) having only primary school education. Chi-square statistics at 0.01 probability level showed that tree husbandry is not strange to farmers and that farm forestry farmers were convinced on the importance of frees on farms. The analyses further revealed that OYSADEP extension agents were not providing incentives to encourage private participation in agroforestry practice; that OYSADEP extension personnel had no formal training in forestry and that OYSADEP was not favorably disposed to agroforestry extension. All these showed that rural farmers were aware of the importance of trees on farm, although not through OYSADEP extension network.